2004
DOI: 10.1111/j.1365-2699.2004.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Cerberus (Serpentes: Homalopsinae) and phylogeography of Cerberus rynchops: diversification of a coastal marine snake in Southeast Asia

Abstract: Aim The biogeography of Southeast Asia has been greatly affected by plate tectonic events over the last 10 Myr and changing sea levels during the Quaternary. We investigated how these events may have influenced the evolution of Cerberus Cuvier, a marine coastal snake belonging to the Homalopsinae (Oriental-Australian Rear-fanged Water Snakes). This study is an expansion of a previous study on the biogeography and systematics of Cerberus.Location We obtained species from localities across the range of the widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…(2) Are the patterns of genetic diversity in Philippine Cyrtodactylus similar to those noted in other lineages (Jones and Kennedy, 2008;McGuire and Kiew, 2001;Steppan et al, 2003;Alfaro et al, 2004)? We evaluated each question using the approximately unbiased (AU) test (Shimodaira and Hasegawa, 2001;Shimodaira, 2002).…”
Section: Topology Tests and Amovasmentioning
confidence: 93%
See 2 more Smart Citations
“…(2) Are the patterns of genetic diversity in Philippine Cyrtodactylus similar to those noted in other lineages (Jones and Kennedy, 2008;McGuire and Kiew, 2001;Steppan et al, 2003;Alfaro et al, 2004)? We evaluated each question using the approximately unbiased (AU) test (Shimodaira and Hasegawa, 2001;Shimodaira, 2002).…”
Section: Topology Tests and Amovasmentioning
confidence: 93%
“…In a study of Cerberus water snakes, Alfaro et al (2004) found strong support for Luzon populations of C. rhynchops to be sister to a clade of western Visayan populations of C. rhynchops and C. microlepis from Luzon. McGuire and Kiew (2001) found strong support for a Mindoro + Sibuyan (Romblon Province) clade within Draco quadrasi, support for the polyphyly of Luzon D. spilopterus, and support for a Luzon + Western Visayan clade within D. spilopterus.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is also differentiated between the Indian Ocean and South China Sea and has a similar phylogeographic story with C. tagal of sea-level changes and surface currents influencing the present-day genotype distribution (Alfaro et al 2004). The isolation by the Sunda Land is also reflected in the genetic differentiation of the Kuda seahorse, Hippocampus kuda, in the Indian and Pacific Oceans (Lourie et al 2005).…”
Section: Phylogeography Of C Tagal In Southeast Asiamentioning
confidence: 97%
“…Hence, it is possible that the Sunda shelf/Indo-Pacifc biogeographic barrier that formed during low sea level stands isolated populations of H. curtus and many other species of sea snakes spanning the IO and WP. Interestingly, this pattern has also been observed in recent phylogeographic studies of two other aquatic snakes: the salt water tolerant amphibious Cerberus rynchops (Alfaro et al, 2004;Murphy et al, 2012) and the viviparous sea snake Hydrophis cyanocinctus (Sanders et al, 2013b). Many marine fishes (Magsino and Juinio-Meñez, 2008;Gaither et al, 2011) and invertebrates (Lavery et al, 1996;Benzie, 1999;Crandall et al, 2008) also show this pattern of Indo-Pacific vicariance.…”
Section: Past and Present Barriers To Dispersal And Gene Flow Betweenmentioning
confidence: 65%